2013
DOI: 10.1177/0040517512470199
|View full text |Cite
|
Sign up to set email alerts
|

The effects of various lubricants on the friction properties of sewing threads

Abstract: This paper describes an experimental investigation into the effects of different types and amounts of lubricants on the friction properties of sewing threads. In this work, four types of sewing threads, CO, PET-spun, core-spun (PET/PET) and core-spun (PET/CO) were used. Three different lubricant types and lubricant feeding rates (0.5, 1 and 2 g/min) were applied to the sewing threads. The results of the research show that the type and amount of lubricant have important effects on the friction of the sewing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
18
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 6 publications
(6 reference statements)
1
18
0
2
Order By: Relevance
“…The wearability of harness cord is mainly affected by properties of fibers, structure, surface coating, lubricant and interfacial property [3,4]. The traditional cotton and ramie harness cords are inferior in wearability and are susceptible to environments; thus, they need to be lubricated, waxed or sized [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The wearability of harness cord is mainly affected by properties of fibers, structure, surface coating, lubricant and interfacial property [3,4]. The traditional cotton and ramie harness cords are inferior in wearability and are susceptible to environments; thus, they need to be lubricated, waxed or sized [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent publication, it is reported that the amount and type of the lubricant applied have a profound effect on frictional properties of the thread. Friction can be 200 times lower for thread with lubrication, as compared to thread without lubrication [9][10]. It is found that most of the researchers have focused on the effect of lubrication on frictional properties of the thread but no study has reported the effect of lubrication on sewing thread strength before sewing and during various stages of sewing.…”
Section: Introductionmentioning
confidence: 99%
“…The highest friction coefficient was found for the flax [16]. Gurarda et al examined the effects of lubricants on the friction properties of sewing threads [17]. Ozcelik Kayseri investigated the frictional properties of 100% lyocell, modal and viscose yarns.…”
Section: Introductionmentioning
confidence: 99%